2007
DOI: 10.1200/jco.2006.08.5803
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Multiple Myeloma: Diagnostic and Clinical Implications

Abstract: MRI is a more powerful tool for detection of FLs than is MBS. MRI-FL number had independent prognostic implications; additionally, MRI-FL resolution identified a subgroup with superior survival. We therefore recommend that, in addition to MBS, MRI be used routinely for staging, prognosis, and response assessment in myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
259
0
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(278 citation statements)
references
References 23 publications
1
259
0
17
Order By: Relevance
“…We and others have previously described that diffuse MRI pattern correlates with shorter survival when conventional chemotherapy or novel agent-based regimens are used as first line therapy in symptomatic myeloma [4,5,15]. The Arkansas group showed that the presence of more than seven focal lesions on whole body MRI is also an independent prognostic factor for OS in patients who received thalidomide-based first line therapy [16]. In this study, we showed that patients with diffuse MRI patterns have almost two-fold longer median OS with the use of novel agent-based therapies upfront compared to conventional treatment.…”
Section: Mri Patterns and Cytogenetic Abnormalitiesmentioning
confidence: 95%
“…We and others have previously described that diffuse MRI pattern correlates with shorter survival when conventional chemotherapy or novel agent-based regimens are used as first line therapy in symptomatic myeloma [4,5,15]. The Arkansas group showed that the presence of more than seven focal lesions on whole body MRI is also an independent prognostic factor for OS in patients who received thalidomide-based first line therapy [16]. In this study, we showed that patients with diffuse MRI patterns have almost two-fold longer median OS with the use of novel agent-based therapies upfront compared to conventional treatment.…”
Section: Mri Patterns and Cytogenetic Abnormalitiesmentioning
confidence: 95%
“…88 An alternative explanation might be that these focal lesions, which may be the first site of recurrence, contain cells that are nonsecretory (possibly myeloma stem cells). Therefore, a more precise approach of the CR status might require an imaging technique (magnetic resonance imagery or positron emission tomography-computed tomography scan) in addition to serologic, cytologic, and possibly immunophenotypic analysis.…”
Section: Which Level Of Response Is Necessary?mentioning
confidence: 99%
“…16 Such focal lesions harbor viable tumor cells as shown by 18-fluorodeoxyglucose avidity on PET-CT scanning as well as on cytogenetic and GEP examinations of samples procured from focal lesions under CT guidance. MRI-defined focal lesions, often representing the first site of disease recurrence, can resolve in up to 60% of patients, with a median lag time behind onset of clinical CR of 24 months.…”
Section: Figurementioning
confidence: 99%